2013
DOI: 10.7314/apjcp.2013.14.7.4347
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism Underlying Hesperetin-induced Apoptosis by in silico Analysis and in Prostate Cancer PC-3 Cells

Abstract: Aim: To investigate the molecular mechanisms underlying triggering of apoptosis by hesperetin using in silico and in vitro methods. Methods: The mechanism of binding of hesperetin with NF-kB and other apoptotic proteins like BAX, BAD, BCL 2 and BCL XL was analysed in silico using Schrodinger suite 2009. In vitro studies were also carried out to evaluate the potency of hesperetin in inducing apoptosis using the human prostate cancer PC-3 cell line. Results: Hesperetin was found to exhibit high-affinity binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 21 publications
(17 reference statements)
1
27
0
1
Order By: Relevance
“…NF-kB regulates the expression of both antiapoptotic and proapoptotic genes. It is a family of closely related protein dimers that bind to a common sequence motif in DNA the kB site (Shanmugam et al, 2013). p50p65 dimer is the the most common active form of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB regulates the expression of both antiapoptotic and proapoptotic genes. It is a family of closely related protein dimers that bind to a common sequence motif in DNA the kB site (Shanmugam et al, 2013). p50p65 dimer is the the most common active form of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Generally NF-ĸB is residing in the cytoplasm, once activated by various signals translocated into the nucleus and regulates the expression of both anti-apoptotic and pro-apoptotic genes. Recently some of the target genes activated by NF-ĸB (cyclin D1, Bcl-2, Bcl-XL, matrix metallo-proteinases (MMPs) and VEGF) which are very important for cellular transformation, cell proliferation, invasion, migration and metastasis (Sambantham et al, 2013). The other report explains either up-regulation of Bax or decrease in the Bcl-2 protein level after treatment with various cancer drugs resulting in mitochondrial mediated apoptosis (Wan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The primary anti-apoptotic and pro-apoptotic members of the Bcl-2 family regulate apoptosis by controlling mitochondrial function (19). Bcl-2 inhibits apoptosis by preventing an increase in cytoplasmic calcium concentration (6). In previous studies, Bcl-2 expression has been observed to be a notable feature in certain human malignant tumors; and Bcl-2 is now believed to be an anti-apoptotic gene that promotes tumor occurrence through inhibiting apoptosis and prolonging the survival of cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced apoptosis and increased proliferation are thought to be the primary mechanisms underlying the formation of the majority of tumors. Inhibition of apoptosis may also possess a significant role in the progression of prostate cancer, and B-cell lymphoma-2 (Bcl-2) is thought to be one of the most significant genes required for apoptosis (6).…”
Section: Introductionmentioning
confidence: 99%